PERENCANAAN DAN PERANCANGAN TERMINAL PENUMPANG PELABUHANA KALIANGET DENGAN PENDEKATAN ECO-TECH ARCHITECTURE - Purnama Sakhrial Pradini; Sarwo Edy; Tigor David Manalu; Rizal Fandani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2021)
The passenger terminal is a much-needed facility for the public or tourists in Sumenep Regency, because of the conditions in the field that already have a port but do not have adequate terminal facilities. Passengers have always been faced with discomfort when waiting for a ship to dock and also the emergence of a negative stigma in the community that the port is a slum place, causing issues that must be resolved immediately. The design of the passenger terminal at Kalianget port, Sumenep Regency, is closely related to architectural principles by applying a combination of ecological concepts and architectural technology. The purpose of this design is to produce a Design of the Kalianget Port Passenger Terminal which can increase the number of users and tourists who will visit the surrounding islands. The benefits of this design are that it can improve the economy, regional image and open jobs for the surrounding community and eliminate the bad stigma in society regarding a slum port. This design uses the Eco-Tech Architecture approach, where this theme is very suitable to be applied because the surrounding area is very supportive of the application of 6 principles to Eco-Tech architecture. where in outline this concept has a goal to protect each other between the built environment and the natural environment.